2007
DOI: 10.1093/ietcom/e90-b.11.3061
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Heavy-Hitter Flows from Sampled Flow Statistics

Abstract: SUMMARYWith the rapid increase of link speed in recent years, packet sampling has become a very attractive and scalable means in collecting flow statistics; however, it also makes inferring original flow characteristics much more difficult. In this paper, we develop techniques and schemes to identify flows with a very large number of packets (also known as heavy-hitter flows) from sampled flow statistics. Our approach follows a two-stage strategy: We first parametrically estimate the original flow length distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…The characterization of big IP flows in large scale optical networks has also been addressed in other research works [13] [14] [15] [16] [12]. From this related work, we highlight the following two investigations, due to some similarities to this paper.…”
Section: Related Workmentioning
confidence: 83%
See 1 more Smart Citation
“…The characterization of big IP flows in large scale optical networks has also been addressed in other research works [13] [14] [15] [16] [12]. From this related work, we highlight the following two investigations, due to some similarities to this paper.…”
Section: Related Workmentioning
confidence: 83%
“…The knowledge of the heavy-hitter 1 [12] of flows originated from these applications allows network managers to establish lambda-connections in advance for such flows. However, there may be also other big IP flows in current networks that could also benefit from being moved to lambda-connections, but for some reason (e.g., the network manager may not be aware of their existence) they may not be selected.…”
Section: Introductionmentioning
confidence: 99%
“…Although packet sampling provides greater scalability for network measurements [11,[15][16][17][18], it makes inferring the original traffic characteristics much more difficult and biased because it is inherently lossy. For example, Kawahara et al [19] showed that network anomalies generating a large number of small flows, such as network scans or SYN flooding, become difficult to detect during packet sampling.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Besides, numerous researchers have discussed the issues related to considered flow accuracy when measuring local area network traffic (Amer 1982;Chlamtac 1980;Jain and Routhier 1986). Because high packet-rate flows have a great impact on network performance, their prompt identification is important in network management and traffic engineering (Mori et al 2007).…”
Section: Introductionmentioning
confidence: 99%